2023
DOI: 10.4266/acc.2023.00570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of admission GCS score to admission GCS-P and FOUR scores for prediction of outcomes among patients with traumatic brain injury in the intensive care unit in India

Abstract: Background: This study aimed to determine the predictive power of the Full Outline of Unresponsiveness (FOUR) score and the Glasgow Coma Scale Pupil (GCS-P) score in determining outcomes for traumatic brain injury (TBI) patients. The Glasgow Outcome Scale (GOS) was used to evaluate patients at 1 month and 6 months after the injury. Methods: We conducted a 15-month prospective observational study. It included 50 TBI patients admitted to the ICU who met our inclusion criteria. We used Pearson’s correlation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“… 5 , 6 , 17 On comparison of GCS and GCS-P, the latter is considered a better predictor of outcome than GCS alone. 15 , 16 Our study found all three coma scores to be comparable for prediction of mortality and 3 months poor outcome, which is in agreement with another recent study by Agrawal et al 18 This can be largely due to differences in study design, severity of TBI in sampled patients and sample size in the earlier studies.…”
Section: Discussionsupporting
confidence: 91%
“… 5 , 6 , 17 On comparison of GCS and GCS-P, the latter is considered a better predictor of outcome than GCS alone. 15 , 16 Our study found all three coma scores to be comparable for prediction of mortality and 3 months poor outcome, which is in agreement with another recent study by Agrawal et al 18 This can be largely due to differences in study design, severity of TBI in sampled patients and sample size in the earlier studies.…”
Section: Discussionsupporting
confidence: 91%
“…The GCS is a widely used scale for assessing the level of consciousness, with scores ranging from 3 to 15. Previous studies have consistently demonstrated the importance of the GCS score in evaluating the severity of neurological disorders 21 , 25 , 26 . The SOFA score serves as a valuable tool for quantifying the extent of organ dysfunction or failure at the point of ICU admission and has found widespread application in predicting in-hospital mortality in this setting 27 29 .…”
Section: Discussionmentioning
confidence: 92%